Pengaruh Harga, Kualitas Produk, Dan Layanan Minat Beli Sosis Daging Sapi Di Kota Malang - H Lende, Agustinus; Suroto, Karunia Setyowati; Rinanti, Rosyida Fajri; Murti, Ariani Trisna (Jurnal Ilmiah Fillia Cendekia, 2025)
With a population of 847,182 people and an area of ​​3,530.65 km2, Malang City produces 3,887,589 kg of beef in 2021 and 4,300,736 kg in 2022. The approach used in quantitative descriptive research is Purposive Sampling. This research sample uses a 10% Slovin objective sample to select a sample of 100 people based on the results of a survey of 1,950 visitors to Pasar Besar and Pasar Oro-Oro Dowo in Malang City. Product price has a positive effect on sales, with a t-table of 4.153-1.985 and a significance level of 0.000-0.05. Based on the calculated t-table of 4.173-1.985 and a significance value of 0.000-0.05, consumer willingness to buy is significantly influenced by the quality of the goods. The calculated t-table of -3.769 ± 1.985 and the significance value of 0.000 ± 0.05 indicate a fairly high correlation between service quality and purchasing decisions. The purpose of this study is to find the impact of factors such as price, product or service quality, and customer interest. The combined impact of X1, X2, and X3 on Y is 0.000 ± 0.05, which is a noteworthy amount. Keywords: Price, product quality, service quality and purchasing interest